2023
DOI: 10.3390/insects14020194
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Roles of Insect Carboxyl/Cholinesterases in Chemical Adaptation

Abstract: Insects have evolved several intricate defense mechanisms to adapt to their chemical environment. Due to their versatile capabilities in hydrolytic biotransformation, insect carboxyl/cholinesterases (CCEs) play vital roles in the development of pesticide resistance, facilitating the adaptation of insects to their host plants, and manipulating insect behaviors through the olfaction system. CCEs confer insecticide resistance through the mechanisms of qualitative or quantitative changes of CCE-mediated enhanced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 131 publications
2
20
0
Order By: Relevance
“…We successfully constructed a Bt + hpPxCHS1-pyramid transgenic oilseed rape and observed that the pyramid Bt + hpPxCHS1transgenic oilseed rape reduced the survival rate of DBM larvae and accelerated their death compared to Bt-transgenic oilseed rape and RNAi treatment group. This finding is consistent with other studies, 34,35 where transgenic cotton pyramids were more effective than RNAi cotton in insect control. 16 Kim et al 43 reported that the suppression of the midgut SeCHS-B gene significantly increased the mortality of the third instar larvae of Spodoptera exigua to 34% in 10 μg Cry1Ac protein and 29% in 0.8 μg Cry1Ac protein at 6 days after treating, enhancing the larvae's sensitivity of larvae to Cry1Ac and Cry1Ca genes against Spodoptera exigua.…”
Section: The Efficacy Of Bt + Hppxchs1-pyramid Transgenic Plants To C...supporting
confidence: 93%
See 2 more Smart Citations
“…We successfully constructed a Bt + hpPxCHS1-pyramid transgenic oilseed rape and observed that the pyramid Bt + hpPxCHS1transgenic oilseed rape reduced the survival rate of DBM larvae and accelerated their death compared to Bt-transgenic oilseed rape and RNAi treatment group. This finding is consistent with other studies, 34,35 where transgenic cotton pyramids were more effective than RNAi cotton in insect control. 16 Kim et al 43 reported that the suppression of the midgut SeCHS-B gene significantly increased the mortality of the third instar larvae of Spodoptera exigua to 34% in 10 μg Cry1Ac protein and 29% in 0.8 μg Cry1Ac protein at 6 days after treating, enhancing the larvae's sensitivity of larvae to Cry1Ac and Cry1Ca genes against Spodoptera exigua.…”
Section: The Efficacy Of Bt + Hppxchs1-pyramid Transgenic Plants To C...supporting
confidence: 93%
“…In total, CCE, v-ATPas, CYP6CV2, and CHS1 were selected as candidate target genes as they were reported for effective control in Lepidoptera insects. 33,34 To identify the most suitable target gene for RNAi, we employed quantitative real-time polymerase chain reaction (qRT-PCR) to measure the transcription expression of CHS1, V-ATPase, CCE, and CYP6CV2 gene in DBM for five growth ages (first instar, second instar, third instar, fourth instar, and pupa). The results showed that the CHS1 gene was expressed at the five stages, with higher relative expression at the third instar and pupa stages (Supporting Information Fig.…”
Section: Selection Of Target Genes and Dsrna Synthesis Of The Chs1 Genementioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides mentioned above are all facing a similar dilemma of increasingly enhanced resistance owing to gene variation of the target protein. More resistance is coming with overdosed and broad-spectrum pesticide usage, leading to larger dosages of pesticides to realize the same effect compared with the past [ 40 , 41 ]. It is to say that the economic benefit brought by pesticides is decreasing while the environmental burden is increasing.…”
Section: Mechanisms and Hazards Of Pesticidesmentioning
confidence: 99%
“…These enzymes constitute a heterogeneous and multifunctional system whose function is related to the hydrolysis of esters (Oakeshott et al., 2005). It is also implicated in various metabolic processes in insects, such as food digestion (Campbell et al., 2003; Healy et al., 1991), reproductive biology (Chertemps et al., 2012; Krishnamoorti & Singh, 2017), and insecticide degradation (Cruse et al., 2023).…”
Section: Introductionmentioning
confidence: 99%